(3aJM GdYRjR TQM GdhLjRs - (3YHO GdcQje Hf eMeO Hf YHO GdcQje, CHh GdbGSe GdQGaYj GdbRhjfj,J (B623 (3g` s; (3GdZRGdj , MLI GdESdGe CHh MGeO eMeO Hf eMeO GdZRGdj GdTGaYj GdWhSj, MLI GdGSdGe GdZRGdj,J (B505 (3g` s ((3Ydi Hf YHO GdQMef Hf YeQ Hf YHO GdhgGH Hf eMeO Hf WGgQ GdOeTbi s)
(3ChdgG (B:s
(3bGd GdEeGe GdZRGdi MLI GdESdGe QMeg Gddg GdHGH GdQGHY BNQ GdaUd GdChd ai GdcdGe eYghO hai GdbQBf hGdSfI ehLhO s
(3BNQgG (B:s
(3hbhdg aEf de jMda Ydjg dG ENJUGU dg HgPg GdUhQg Ydi eG HjfGg hHGddg GdJhajb fLR BNQ QHY GdfcGM hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3Gdabg GdTGaYjs